Looking into a live subject (R & D : reading for the R & D community, 2003)
The IVIS 300 In Vivo Imaging System, developed by a research team at Xenogen Corp, Alameda, CA, is discussed as a winner of R&D Magazine's 41st Annual R&D 100 Awards. This in vivo luminescence imaging system, and associated reconstruction software, improves spatial resolution and allows users to determine the location of a light-emitting object in tissue to within 1-3 mm, depending on the depth.